Outcomes after EVAR in females are similar to males - Tumer, Naim Boran (BMC Cardiovasc Disord, 2021)
INTRODUCTION: Women are less likely to develop infrarenal abdominal aortic aneurysm; however, when they do, it is almost always associated with challenging anatomy, more rapid aneurysmal growth rate and earlier rupture. Women generally have poorer outcomes following open aneurysm repair; and in this respect, the present study aims to evaluate if it is so after endovascular repair. METHODS: A retrospective analysis of our database was performed for patients underwent endovascular aneurysm repair (EVAR) between January 2013–March 2020. 249 elective EVAR patients were evaluated. Patients were categorized according to gender and 26 patients (10.4%) were female. Demographics and pre-peri-postoperative findings were compared. Propensity score matching (ratio 1:1) was performed to reduce selection bias. RESULTS: In the overall unmatched cohort, female population had more diabetes mellitus (p = 0.016) and hypertension (p = 0.005). However, coronary artery disease (p = 0.005) and coronary artery bypass grafting (p = 0.006) were more in male gender. Non-IFU implantation was higher in female group (38.5% vs. 11.5%, p = 0.025). After propensity matching, even though it was not statistically significant, early mortality for female gender was higher when compared to male gender (7.7% and 0%, respectively, p = 0.490). In the follow-up period, no difference in all-cause mortality, secondary interventions or complications have been observed between the genders. CONCLUSION: Challenging anatomy and subsequently treated patients outside IFU may be the reasons for higher morbidity and mortality in women. However, despite these factors female and male patients revealed equivalent early and late results.